Retention of locally injected human iPS cell-derived cardiomyocytes into the myocardium using hydrolyzed gelatin - Jun Iida; Kazuki Kotani; Kozue Murata; Keisuke Hakamada; Wusiman Maihemuti; Yoshinobu Mandai; Yosuke Hiraoka; Kenji Minatoya; Hidetoshi Masumoto (Scientific Reports)
Abstract This study explored the impact of hydrolyzed gelatin (HG) concentration on the retention and therapeutic efficacy of human iPS cell-derived cardiomyocytes (hiPSC-CMs) when injected into the myocardium. The solubility of HG allows precise control over its concentration, influencing the distribution and leakage of injected solutions, which may affect therapeutic outcomes. Using both ex vivo and in vivo rat models, we investigated how varying HG concentrations affect the retention of solution and diffusion within the myocardium. In ex vivo static rat hearts, 10% HG minimized leakage but allowed significant diffusion. However, in pulsating in vivo hearts, 20% HG provided the best retention. In a rat myocardial infarction model, hiPSC-CMs suspended in 20% HG resulted in the highest cell retention. Echocardiogram showed a significant increase in the ejection fraction two weeks after transplantation compared to before transplantation. Additionally, cardiac magnetic resonance imaging (MRI) revealed that the ejection fraction was significantly higher than that of the sham group four weeks after transplantation. These findings suggest that optimizing HG concentration is crucial for enhancing the retention and therapeutic efficacy of hiPSC-CM transplants in treating heart disease.